The conservation value of forest fragments and oil palm plantation for mammals in Sabah Malaysian Borneo - Esther Lonnie Baking (2012)
The rapid and extensive expansion of the agricultural sector, especially planting of oil palms in Sabah are affecting the natural resources considerably. Areas under natural forest cover are being reduced and fragmented resulting in many isolated forest islands located within the converted habitat matrix of agriculture crop. The present study was conducted in a lowland dipterocarp rainforest of Tabin Wildlife Reserve, in Lahad Datu, Sabah, and in the surrounding oil palm plantations that were interspersed with highly degraded isolated forest fragments. The objectives were to assess the values of forest fragments in terms of species compositions, richness and diversity of mammals utilizing the forest fragments, and to assess the effects of retaining forest fragments in oil palm plantation on the small mammal species richness, abundance, diversity and compositions. Twelve trapping sessions using camera traps, direct observations and small mammal traps have been successfully carried out from May 2009 to April 2010. The trapping-sites include one primary forest, three of isolated forest fragments (4.84 ha, 16.07 ha and 26.75 ha) and four oil palm plantations. Overall, 1,913 individual photographs representing 28 species and 15 families of mammals have been recorded by camera trapping. When the mammal species richness were compared between forest habitat and forest fragments, there were 49%, 69% and 65% decrease in the number of mammal species recorded respectively in forest fragments in order of increasing distance from the forest habitat. The forest fragments resulted in the changes of species composition with some species that were recorded as abundant in forest habitat were absent in the forest fragments e.g. Tragulus sp. and Cervus unicolor. However, the Prionailurus bengalensis were found to exist in all forest fragments. For small mammal community, based on 5,220 trap-nights of live trapping, there were 349 animals captured represented by 18 species. The oil palm habitats recorded only six species of small mammal and were highly dominated by Rattus rattus. The percentage of trap success based on all capture events was 6.69%. In conclusion, the forest fragments have provided some habitats for some species of mammals, but both the forest fragments and oil palm habitats harboured very low mammal species richness. However, retaining the forest fragments in the oil palm plantations do not increase the value of the oil palm plantation with respect to the mammal faunas and does not have any effect on controlling the abundance of pest species (rodent) in oil palm plantation.